2017
DOI: 10.1371/journal.pone.0173630
|View full text |Cite
|
Sign up to set email alerts
|

The myodural bridge existing in the Nephocaena phocaenoides

Abstract: Recent studies have identified that the myodural bridge (MDB) between the rectus capitis posterior minor (RCPmi) and the cervical spinal dura mater in the posterior atlanto-occipital interspace in humans. And it was supposed that the MDB may play essential physiological roles. As a result, the MDB is possibly a highly conserved structure in the evolution of mammals. However, there is little confirmative description about the existence of the MDB in marine mammals. The objective of this study was to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
1
26
1
Order By: Relevance
“…The MDB has been found in the suboccipital region of quadrupedal terrestrial mammals, which includes cats, rats, dogs, rabbits, guinea pigs, macaques, and mandrill [ 25 ], as well as one reptilian species (the siamensis crocodile) [ 26 ]. Regarding marine mammals, we recently confirmed the existence of the MDB in the finless porpoise ( Neophocaena phocaenoides ) [ 27 ]. In this study, we confirmed the existence of the MDB in the sperm whale via multiple research methods.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The MDB has been found in the suboccipital region of quadrupedal terrestrial mammals, which includes cats, rats, dogs, rabbits, guinea pigs, macaques, and mandrill [ 25 ], as well as one reptilian species (the siamensis crocodile) [ 26 ]. Regarding marine mammals, we recently confirmed the existence of the MDB in the finless porpoise ( Neophocaena phocaenoides ) [ 27 ]. In this study, we confirmed the existence of the MDB in the sperm whale via multiple research methods.…”
Section: Discussionmentioning
confidence: 88%
“…The fact that MDB exists universally in mammals has been reported only in a few studies so far. Our previous studies have proved the existence of the MDB in seven terrestrial mammal orders [ 25 ], one reptilian species (the siamensis crocodile) [ 26 ] and six finless porpoise ( Neophocaena phocaenoides ) [ 27 ]. The objective of this study is to examine the morphology of the MDB within other marine mammals and to discuss possible physiological functions from an evolutionary perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The myodural bridge (MDB) is a connective tissue band that connects the suboccipital muscles and nuchal ligament (NL) with the cervical spinal dura mater (SDM) [1][2][3][4][5][6]. It has been recently confirmed as a conserved structure in mammals [7][8][9]. The MDB has a critical role in transmitting tensile force from its muscular and ligamentous components to the SDM, which has an essential role in the etiology of headache and cervicocephalic pain syndrome [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to rencent reports, MDB dysfunction may occur with pathological conditions of the RCPmi muscle, resulting in the generation of cervicogenic headache, and other craniofacial disorders [13][14][15][16][17]. In recent years, researchers have found that the MDB is a universal structure in mammals [18], including marine mammals (Nephocaena phocaenoides and sperm whales) [19,20]. The MDB also exists in reptiles (Siamese crocodile and Trachemys scripta elegans) [21,22], as well as in birds (Rock pigeons and Gallus domesticus) [23,24].…”
Section: Introductionmentioning
confidence: 99%